2011
DOI: 10.5249/jivr.v3i1.28
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic injuries in pregnant women: A case of motor vehicle accident for "Ground Round" discussion

Abstract: Abstract:The main objective for introducing this case study is to create a platform from which the importance of road traffic related injuries and traumas can be emphasized and discussed within and across various fields of investigation. The long term goal is to entice public campaign around unmet needs for higher road safety measures to reduce primary, secondary, and tertiary risks of injuries and traumas. Case:A 28-year-old pregnant woman with a 16-week gestational age fetus was involved in a road car crash … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Furthermore, since there are few studies regarding osteolytic lesions in pregnancy and no data on the treatment of such femoral fractures in the literature, to the best of our knowledge, the present case report is the first to report the management of pathological femoral fracture secondary to breast cancer in pregnancy. Traumatic injuries are detected in 6-7% of pregnant women (10). These are the most common non-obstetric risk factors for miscarriage and preterm delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, since there are few studies regarding osteolytic lesions in pregnancy and no data on the treatment of such femoral fractures in the literature, to the best of our knowledge, the present case report is the first to report the management of pathological femoral fracture secondary to breast cancer in pregnancy. Traumatic injuries are detected in 6-7% of pregnant women (10). These are the most common non-obstetric risk factors for miscarriage and preterm delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Damage control orthopedic principles are applied when early total care is impossible (11). In addition, previous studies have reported rare cases of fractures due to transient osteoporosis during pregnancy, which may be treated with internal fixation or arthroplasty (10,12).…”
Section: Discussionmentioning
confidence: 99%
“…Such patients, therefore, are more likely to respond differently to anesthetic agents. In reference to the current case, 1 we do not have any data to show patient’s blood pressure, heart rate, respiratory rate and urine output. However, according to her medical chart, we do know that her estimated blood lost was 10-15%.…”
mentioning
confidence: 99%